Euthanasia in persons with advanced dementia: a dignity-enhancing care approach - Gómez-Vírseda, Carlos (Journal of medical ethics, 2022)
In current Western societies, increasing numbers of people express their desire to choose when to die. Allowing people to choose the moment of their death is an ethical issue that should be embedded in sound clinical and legal frameworks. In the case of persons with dementia, it raises further ethical questions such as: Does the person have the capacity to make the choice? Is the person being coerced? Who should be involved in the decision? Is the person’s suffering untreatable? The use of Advance Euthanasia Directives (AED) is suggested as a way to deal with end-of-life wishes of persons with dementia. However, in the Netherlands—the only country in which this practice is legal—the experiences of patients, doctors, and relatives have been far from satisfactory. Our paper analyses this complex ethical challenge from a Dignity-Enhancing Care approach, starting from the Dutch experiences with AED as a case. We first consider the lived experiences of the different stakeholders, seeking out a dialogical-interpretative understanding of care. We aim to promote human dignity as a normative standard for end-of-life care practices. Three concrete proposals are then presented in which this approach can be operationalised in order to deal respectfully with the end-of-life choices of persons with dementia.